Inovasi Pengembangan Kurikulum Hilda Taba Berbasis Pendidikan Islam (Studi Kasus di TK Kartini): Hilda Taba Curriculum Development Innovation Based on Islamic Education (Case Study in Kartini Kindergarten) - Nurhusni; Intan Permata Putri; Sukiman (Universitas Ngudi Waluyo, 2023)
Curriculum is one of the important elements in the education system. In the learning process to keep abreast of the times, the curriculum needs to be innovative development. There are many types of curriculum development models, one of which is the Hilda Taba development model. Hilda Taba's development model focuses more on teacher attention in developing the educational curriculum used in an educational institution. The research method used in this study is a qualitative form with a case study approach. The research subjects were the principal and teachers at Kartini Kindergarten as informants. Methods of data collection using in-depth interviews. The data analysis technique uses the Miles and Huberman method with several stages, namely data reduction, data presentation, drawing conclusions and verification. The triangulation used to test the validity of the data is source and method triangulation. The results of the study show that Kartini Kindergarten has used the Hilda Taba development model in carrying out curriculum development by paying attention to several aspects such as diagnosing needs, formulating educational goals, selection and organization of content as well as selection and organization of learning experiences. Â ABSTRAK Kurikulum sebagai salah satu elemen penting dalam sistem pendidikan. Dalam proses pembelajaran agar terus mengikuti arus perkembangan zaman maka kurikulum perlu dilakukan inovasi pengembangan. Ada banyak jenis model pengembangan kurikulum salah satunya yaitu model pengembangan Hilda Taba. Model pengembangan Hilda Taba lebih memfokuskan kepada perhatian guru dalam mengembangkan kurikulum pendidikan yang digunakan dalam sebuah lembaga pendidikan. Metode penelitian yang digunakan dalam penelitian ini adalah bentuk kualitatif dengan pendekatan studi kasus. Subyek penelitian adalah Kepala Sekolah dan guru di TK Kartini sebagai informan. Metode pengumpulan data menggunakan wawancara mendalam. Adapun teknik analisis data menggunakan metode Miles dan Huberman dengan beberapa tahapan yaitu reduksi data, penyajian data, penarikan kesimpulan dan verifikasi. Triangulasi yang digunakan untuk menguji keabsahan data adalah triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa di TK Kartini telah menggunakan model pengembangan Hilda Taba dalam melakukan pengembangan kurikulum dengan memperhatikan beberapa aspek seperti diagnosis kebutuhan, merumuskan tujuan pendidikan, seleksi dan organisasi isi serta seleksi dan organisasi pengalaman belajar.